INSOLVENSI OPERASIONAL VS KRISIS LEVERAGE: ANALISIS KOMPARATIF PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN Z-SCORE DAN SPRINGATE (Studi Kaus: Pada PT Indofarma Tbk dan PT Pyridam Farma Tbk) - Zaza Dhina Tri Pamungkas (Komunitas Manajemen Kompetitif, 2026)
Abstract: The health sector, particularly the pharmaceutical industry, faces highly complex macroeconomic dynamics in the post-COVID-19 era. After recording windfall profits during the 2020-2021 period, several companies subsequently experienced a drastic contraction in performance during the transition to the endemic phase (2022-2024) due to decreased demand, high operational costs, and swelling debt burdens. Cumulatively, these conditions have driven companies toward financial distress. This quantitative descriptive research aims to analyze and compare the probability of bankruptcy and the anatomy of financial crises between State-Owned Enterprises (SOEs) and private companies. A case study was conducted on PT Indofarma Tbk (INAF), representing an SOE with an acute solvency crisis (operational insolvency), and PT Pyridam Farma Tbk (PYFA), a private entity facing over-leveraging risks due to aggressive debt expansion. This study employs the Altman Z-Score and Springate bankruptcy prediction models to analyze financial data from the 2021–2024 period. Through a comparative approach, this research is expected to uncover differences in the characteristics of financial distress based on ownership status, particularly concerning the Soft Budget Constraint phenomenon in SOEs compared to market discipline in private companies.